2012
DOI: 10.4321/s1695-61412012000300004
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la calidad de vida de los usuarios de hemodiálisis

Abstract: Métodos: Estudio multicéntrico, cuantitativo. Datos colectados de abril a agosto-2010. De los usuarios inivitados (102), 77 aceptaron. Instrumentos utilizados: caracterización sociodemográfica, Kidney Disease and Quality of Live-Short Form (KDQOL-SF TM). Resultados: Mayoría (70,1%) hombres, 50-70 años de edad, 59,7% casados, con hijos, baja escolaridad (76,6%), 79,2% jubilados. 48,8% evaluaron salud como regular y 44,2% como buena. Dimensiones con menores escores medios: "situación de trabajo" (20,78), "funció… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
2
2
0
7
Order By: Relevance
“…Most participants lived with companion, were married and had children. Similar result was obtained by research developed by the Nephrology Unit of a size IV hospital where 77 patients were submitted to hemodialysis 12 . This result shows that patients may count on family support aiming at better coping with chronic disease, being aware that family presence and support may minimize possible physical, emotional and socio-economic injuries caused by chronic disease.…”
Section: Discussionsupporting
confidence: 74%
“…Most participants lived with companion, were married and had children. Similar result was obtained by research developed by the Nephrology Unit of a size IV hospital where 77 patients were submitted to hemodialysis 12 . This result shows that patients may count on family support aiming at better coping with chronic disease, being aware that family presence and support may minimize possible physical, emotional and socio-economic injuries caused by chronic disease.…”
Section: Discussionsupporting
confidence: 74%
“…With respect to age, it was observed that most individuals are in the process of aging or have already reached the third age. Studies corroborate these results, revealing a higher rate of renal patients aged between 51 and 70 years [12][13][14]. It is evident that the world population is living longer.…”
Section: Discussionsupporting
confidence: 75%
“…Os resultados mostraram que o tratamento mantém a vida, alivia sintomas, previne complicações (impedindo a evolução da doença) e promove o bom relacionamento com a equipe. Entretanto, o mesmo interfere na qualidade de vida, assim como no trabalho e na função físico-emocional 19 . A segunda pesquisa foi divulgada em 2015 e visou descrever as representações sociais de pessoas com DRC em hemodiálise sobre o processo de adoecimento, realizando uma investigação qualitativa e descritiva.…”
Section: Discussionunclassified